The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.13005/ojc/350423
|View full text |Cite
|
Sign up to set email alerts
|

The use of Silica Supported Nickel-Copper Oxide Catalyst for Photodegradation of Methylene Blue

Abstract: Photodegradation is a save and low cost methods to clean water bodies from some organic pollutants. The method has been developed in term of increasing the efficiency of the degradation capacity of photocatalyst. The photocatalyst working under visible light is the most desirable. The preparation of silica supported nickel-copper oxide [(Ni-Cu)Ox@SiO2] catalyst and the use of the catalyst in the photodegradation of methylene blue in the water are reported. The catalyst was prepared by impregnating the silica s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…1. It is reported that O‐ and OH‐containing compounds reduce the azo group of MO leading to the color discharging of the dye 11,53,54 . In the present study, the catalytic efficiency of Co 3 O 4 was markedly increased after addition of NiO or PdO/Pd indicating the catalytic wet oxidation (CWO) process, which depends on oxygen vacancies to degrade organic pollutants.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…1. It is reported that O‐ and OH‐containing compounds reduce the azo group of MO leading to the color discharging of the dye 11,53,54 . In the present study, the catalytic efficiency of Co 3 O 4 was markedly increased after addition of NiO or PdO/Pd indicating the catalytic wet oxidation (CWO) process, which depends on oxygen vacancies to degrade organic pollutants.…”
Section: Resultsmentioning
confidence: 54%
“…Therefore, incorporated carbonaceous phytochemicals, revealed by GC–MS in Figs 2(d)–(f), facilitated the flow of photogenerated charge carriers (electrons and holes in opposite directions) to prolong electron lifetime, which then utilized light with superior efficiency. Consequently, on the bases of the holes and electrons of mixed oxides as well as the incorporated carbonaceous material, the mechanism of degradation of MO can be explained as follows: 11,40,53–56 e+O2normalO2 normalO2+H2normalOHO2+OH HO2+H2normalOH2O2+OH H2O22OH h++OHOH OH+organic pollutant0.25em()MOdegradation products+CO2+H2normalO …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotabung N-TiO2 hasil sintesis dikarakterisasi menggunakan alat XRD dengan sumber radiasi Cu Kα Gambar 1 menunjukkan bahwa material hasil sintesis N-TiO2 pada variasi suhu hidrotermal diasumsikan memiliki struktur nanotabung dengan ditandai munculnya puncak dibawah 20º sekitar pada 2 = 11º namun kemungkinan mengalami ketidakstabilan yang berakibat puncak bergeser dikarenakan puncak belum terlalu jelas terlihat [6,9,12]. Perubahan intensitas pada puncak difraktogram hasil sintesis variasi suhu hidrotemal mempengaruhi struktur kristalografi dan morfologi serta sifat fisika-kimia [6,8]. Berdasarkan data yang diperoleh, ukuran kristal setiap fase dihitung berdasarkan nilai FWHM dengan menggunakan persamaan Debrye-Scherrer.…”
Section: Analisis Karakterisasi N-tio2unclassified